Small EU member states and Brexit: Introduction - Ferreira-Pereira, L. C.; Raimundo, A. (Journal of Contemporary European Studies, 2023)
This Special Issue seeks to provide a better understanding of the strategic responses to Brexit from small EU member states. To this end, it links different streams of research and presents innovative inquiries into how ten states positioned themselves in the face of the British exit and with what foreign policy ramifications. More specifically, the collection examines the different countries’ coping strategies vis-à-vis Brexit, the underlying drivers of these responses, as well as their implications for patterns of national foreign policy Europeanization. After presenting the rationale and aims of the collection, this introductory article outlines the comparative framework used by the different contributors in their country studies. It then offers an overview of the main research findings derived from the individual articles. Subsequently, it summarises the comparative findings, with all contributions pointing to significant ‘sheltering’ within the EU, while ‘hedging’ strategies receive greater visibility for the countries most directly affected by Brexit. The overall results also evince a limited Brexit impact upon the foreign policy Europeanization of the countries examined. Finally, this introduction offers a reflection on the main conceptual and empirical ‘pay-offs’ of this Special Issue, closing with some avenues for future research.